Association between COMT Val158Met polymorphism and competition results of competitive swimmers - Abe, D.; Doi, H.; Asai, T.; Kimura, M.; Wada, T.; Takahashi, Y.; Matsumoto, T.; Shinohara, K. (Journal of Sports Sciences, 2018)
Recent studies have shown the contribution of genetic determinants to athletes` physical ability. However, despite the fact that cognitive abilities like self-control and stress-tolerance influence athletes` competitive performance, few studies to date have investigated the association between genetic polymorphism, which is linked to cognitive ability and athletic performance. The present study investigated the link between single-nucleotide polymorphisms (SNPs), which are known to exert influences on dopaminergic neural function and competitive performance of swimmers. The results have revealed superior competitive performance in competitive swimmers with Met allele of catechol-O-methyltransferase Val158Met polymorphism than those with Val/Val genotype. The investigated SNPs of DRD2 and DRD3 were not associated with swimmer`s competitive performance. This finding indicates that genetic polymorphism linked to cognitive ability influences the athletes` performance.